Maternal Ecocriticism and the Ecology of Motherhood in Jean Toomer’s Cane - Wardi, Anissa Janine (Journal of the Motherhood Initiative for Research and Community Involvement, 2016)
In Cane, Jean Toomer illustrates that human corporeality is tethered to the material world, a concept that feminist theorist Stacy Alaimo, in Bodily Natures, refers to as “transcorporeality.” Human bodies are not inured to their environment but are affected by the flow and substances of matter in which they are surrounded. In this modernist text, the natural world is enmeshed with female bodies, both seemingly carrying the dna of the other. The assemblage of the agrarian South, African American women, and scenes of racial violence coalesce and construct a narrative of violated fertility and motherhood. The women of Cane are denied their motherhood because their bodies and being cannot be divorced from the trans-Atlantic trade route, plantation labour practices, and unsustainable logging of old-growth pine forests in post-Reconstruction Georgia. This article examines moments of transcorporeal exchange in Cane (i.e., felled pine trees and fetuses, and maternal bodies and cotton fields) and, in so doing, provides an ecocritical reading of mothering and material interconnectivity—a maternal ecocritical reading—of Toomer’s masterpiece of the Harlem Renaissance.